GW 11: An efficient wheat variety for terminal heat and moisture stress conditions - Agalodiya, A V; Patel, S S; Patel, B N; Yadav, R S; Augustine, N (Journal of Cereal Research, 2011)
Wheat is an important crop worldwide and is grown on about 210 million hectares with annual production of about 648 million metric tons (FAO 2010). The global wheat production should be increased 2% annually until 2020 to meet future demand with the compromise of global warming, end-use quality and newly evolving pathogen and pest populations under reduced water availability as well as under abrupt climatic conditions (especially heat stresses). About 35 percent of irrigated wheat area in Gujarat state is under late sown after cotton and paddy facing heat stress at grain filling stage resulting about 16 percent yield loss as compared to timely sown wheat. Further, North Gujarat and Saurastra regions covering more than 60% wheat area in Gujarat which is prone to water scarcity resulted in drastic reduction in wheat productivity. Therefore, SDAU, Vijapur has developed variety GW 11 having high stable grain yield, better terminal heat tolerance, efficient water utilization, resistance to black & brown rusts and better grain quality for Gujarat state.